2008
DOI: 10.1017/s1049023x0000563x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Problem, Main Objective, and Strategies of Medical Management in Mass-Casualty Incidents Caused by Terrorist Events

Abstract: Based on the experience of managing >20 such events during the last decade, the authors' understanding of a mass-casualty incident is that it is an event in which there may be many victims, but only a few that actually suffer from life-threatening injuries. To make an impact on survival, one must identify those who are severely wounded as quickly as possible and offer those patients opti-mal care. Experienced trauma physicians are the most important resource available to achieve this objective, and they sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The unprecedented death tolls from such incidents in recent years have bolstered calls for developing disaster response plans that can allow hospitals to cope with a sudden influx of trauma [15,16]. Healthcare facilities in the city of Karachi, Pakistan have historically dealt with several terror-related MCEs in previous years [8,[17][18][19][20][21]; however, this incident, in particular, holds the distinctions of being the biggest such event in terms of devastation and the number of fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…The unprecedented death tolls from such incidents in recent years have bolstered calls for developing disaster response plans that can allow hospitals to cope with a sudden influx of trauma [15,16]. Healthcare facilities in the city of Karachi, Pakistan have historically dealt with several terror-related MCEs in previous years [8,[17][18][19][20][21]; however, this incident, in particular, holds the distinctions of being the biggest such event in terms of devastation and the number of fatalities.…”
Section: Discussionmentioning
confidence: 99%
“…Defining the main objective of medical management is crucial in developing a contingency plan for MCIs. 1 Only half of those surveyed indicated that the main objective of the hospital staff after a MCI is the rapid identification of critically injured patients. Only rapid identification and treatment of critically injured patients can reduce the critical mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 In a recent study of 604 victims of MCIs treated between 1995 and 2003, only three (4%) of the 78 critically injured victims were not identified following initial workup in the emergency department. 1 The secondary transfer of victims from one institution to another may be necessary whenever one medical institu-examination of patients are sufficient diagnostics to exclude unidentified blast lung injury, eliminating the need for more sophisticated tests. Seventy-six percent of responders indicated that victims exposed to explosions should be kept under observation for at least 12 hours.…”
Section: Perception Of the Problem And Implications On The Contingencmentioning
confidence: 99%
“…Two aspects should be considered to achieve this 'paradigm shift' in MCI response research: (1) the dynamic and quantitative relationship between surge capacity and vulnerability, and methods for quantitative identification and characterization of vulnerability of a hazard bearing body should be established to study MCI response; (2) the three-dimension framework of MCI management should be confirmed by more practical applications in MCIs. A key to enhance the MCI surge response capability is to improve the suitability of the MCI response planning (Ashkenazi et al, 2008). Vulnerability is very difficult to present under an ordinary status, but vulnerability of a hazard bearing body may be measured by system destruction as well as casualties after disaster attacks.…”
Section: A New Research Paradigm For MCI Management Based On Surge Smentioning
confidence: 99%